RUANG KOMUNITAS DIGITAL DAN BUDAYA - Claresta Felicia; Rudy Trisno (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The issue of covid 19 emerged in 2019 which affected the arrangement of space and the way humans interact. Increasing human dependence on digital media now that will lead to the industrial era 5.0. The needs for both students and work are high, technology inequality in each region. The density of the population and buildings, as well as open space which is only 9.98% is not sufficient for space. Furthermore, it is predicted that 65% of people will live in urban areas by 2050. Based on time, the human way of life will change towards industry 5.0. Digital will play an important role. Human being is important. Human activities that have meaning. In Setu village, Betawi cultural activities are quite thick. The Baritan ceremony is an activity that supports the sustainability of the building. Being and time is modified between culture and technology to produce new experiences. Design method with stages a) Setu environment; b) Issues and issue resolution concepts; c) Design Concept; d)Site Selection and Selected Sites; e) Site; f) Building Mass Concept; g) Zoning and Space Program; h) Facades, exteriors and interiors. The conclusion is the design of the Digital and Cultural Community Space by applying the Contextual concept with the Neo Vernacular style. Keywords: community; covid; culture; digital; industryAbstrakIsu covid 19 muncul ditahun 2019 yang mempengaruhi susunan ruang dan cara manusia berinteraksi. Meningkatkan ketergantungan manusia terhadap media digital sekarang yang akan menuju era industri 5.0. Kebutuhan dari sisi pelajar maupun bekerja tinggi, ketidakmerataan teknologi di setiap daerah. Padatnya penduduk dan bangunan, serta ruang terbuka yang hanya 9.98% tidak mencukupi kebutuhan ruang. Ditambah lagi diprediksikan adanya 65% masyarakat akan tinggal di perkotaan tahun 2050. Berdasarkan waktu, cara hidup manusia akan berubahan menuju industri 5.0. Digital akan mengambil peran penting. Keberadaan manusia penting atau juga being. Aktivitas manusia yang memiliki arti. Di kelurahan Setu, aktivitas budaya Betawi cukup kental. Adanya upacara Baritan sebagai salah satu aktivitas sebagai event yang mendukung keberlangsungan bangunan. Being and time ini dimodifikasi antara kultur dan teknologi menghasikan pengalaman baru. Metode perancangan dengan tahapan a)Lingkungan Setu; b) Isu dan konsep penyelesaian isu; c)Konsep Perancangan; d)Pemilihan Tapak dan Tapak Terpilih; e) Tapak; f)Konsep Massa Bangunan; g) Zoning dan Program Ruang; h)Facade, eksterior, dan interior. Kesimpulan perancangan Ruang Komunitas Digital dan Budaya dengan menerapkan konsep Kontekstual dengan gaya Neo Vernakular.